Analisis Tindak Tutur Direktif Guru dalam Pembelajaran di SMP Negeri 26 Purworejo - Khabib Sholeh; Ica Melvira Pratiwi; Vita Andriliani; Choirotul Umam; Putri Ida Pangestu (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The purpose of this study is to describe the form of teacher directive speech in the learning process at SMP Negeri 26 Purworejo. This study uses a descriptive qualitative approach to provide a detailed overview of the use of speech actions by teachers in teaching and learning activities. The research data is in the form of teachers' speech during the learning process, while the source of the research data is Mr. Deddhy Herrath, S.Pd., as a teacher at SMP Negeri 26 Purworejo. The data collection technique was carried out with free and capable involvement, which allowed the researcher to observe and record the teacher's speech directly in the context of learning. Data analysis is carried out by listening, understanding, organizing, categorizing, and combining between categories based on their context, so that forms of directive speech can be identified systematically. The results of the study show that there are five forms of directive speech, namely asking speech, hope speech, command speech, welcome speech, and asking speech, each of which has its function and context of use in teacher-student interaction. This research is expected to contribute to the development of teachers' communication strategies in learning to be more effective and on target.